Aiming to Improve Readmissions Through InteGrated Hospital Transitions (AIRTIGHT): study protocol for a randomized controlled trial. Issue 1 (December 2016) - McWilliams, Andrew; Roberge, Jason; Moore, Charity; Ashby, Avery; Rossman, Whitney; Murphy, Stephanie; McCall, Stephannie; Brown, Ryan; Carpenter, Shannon; Rissmiller, Scott; Furney, Scott
Abstract Background Hospital readmissions remain highly prevalent despite being the target of policies and financial penalties. Evidence comparing the effectiveness and costs of interventions to reduce readmissions is lacking, leaving healthcare systems with little guidance on how to improve quality and avoid costly penalties. Effective interventions likely need to bridge inpatient and outpatient settings, incorporate information technology, and use dedicated providers. Such complex innovations will require rigorous evaluation. The framework of quality improvement research provides an approach that both improves care locally and contributes to closing the current knowledge gaps for readmissions. In this trial, we will study a comprehensive intervention that incorporates these recommendations into an integrated practice unit, calledtransition services, with an aim of reducing 30-day readmission rates. Methods/design We describe a nonblinded, pragmatic, controlled trial with two parallel groups comprising an evaluation of the effect of referral to a provider-led integrated practice unit, inclusive of comprehensive multidisciplinary care, dedicated paramedicine providers, and virtual visits, on 30-day readmission rates for high-risk hospitalized patients. An automated risk-scoring system will randomly generate referrals to either transition services or usual care for 1520 hospitalized patients who score as high-risk for readmission. Transition services will then engage with patients in the hospital setting using a patient navigator and provide bridging outpatient services for the 30 days following discharge. All outcome data are retrieved electronically from administrative medical records. After reapplication of inclusion and exclusion criteria at the time of hospital discharge, analyses will follow the intention-to-treat principle such that patients will be analyzed on the basis of the referral group to which they were initially randomized. Discussion The hospital transition program under study is complex and integrates the latest recommendations for readmission reduction strategies. As healthcare systems innovate to address readmissions through such complex interventions, there is significant benefit for stakeholders to have a clear understanding of the potential reach, cost, and real-world effectiveness. The pragmatic methods described here provide a template for conducting quality improvement research that fits seamlessly into existing care delivery and improvement efforts, leading to better-informed strategic decisions and the investments necessary to transform care and value for patients. Trial registration ClinicalTrials.gov, NCT02763202 . Registered 3 March 2016 (retrospectively registered).